2019
DOI: 10.1038/s41372-019-0385-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal salivary sex hormone levels and birth-weight-for-gestational age

Abstract: Objective: To determine whether prenatal sex hormones from maternal saliva are associated with birth weight-for-gestational age. Study Design: We measured salivary progesterone, testosterone, estradiol, dehydroepiandrosterone (DHEA) and cortisone in 504 pregnant women in a Mexico City cohort in the. We performed linear and modified Poisson regression to examine associations of log-transformed hormones with birth weight-for-gestational age z-scores and the risk of small-for-gestational age (SGA) and large-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The peak of m/z 289.2162 and RT 4.83 min. is a putative C19 steroid hormone, probably testosterone which have been previously linked with birth weight (42)(43)(44). Both of these peaks passed the 60% coverage cutoff (TH4) but failed to pass the 10,000 peak height in 2% sample cutoff (TH3) and therefore were missed in the original publication's statistical analysis (Table 5).…”
Section: Figure 4 | Rejection Of Biological Relevant Peaks By Peak Height and Detection Frequency Thresholdsmentioning
confidence: 99%
“…The peak of m/z 289.2162 and RT 4.83 min. is a putative C19 steroid hormone, probably testosterone which have been previously linked with birth weight (42)(43)(44). Both of these peaks passed the 60% coverage cutoff (TH4) but failed to pass the 10,000 peak height in 2% sample cutoff (TH3) and therefore were missed in the original publication's statistical analysis (Table 5).…”
Section: Figure 4 | Rejection Of Biological Relevant Peaks By Peak Height and Detection Frequency Thresholdsmentioning
confidence: 99%
“…We found that high maternal T levels were inversely associated with neonatal health outcomes and physical growth. Neonates of mothers with high T levels spent more days in the hospital and showed delayed physical growth in body weight and length between birth and 40 weeks' GA. Svensson et al 25 reported that a high maternal T level was associated with lower birth weight, small for GA, and shorter gestation, which could contribute to less favorable neonatal health outcomes. The associations between high maternal T levels and low birth weight and small for GA remained even after adjusting for maternal age, BMI, parity, secondhand smoke exposure, education, SES, and infant sex.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is contrary to that of Tarca et al, 42 who reported that mean birth weight at 40 weeks' GA was 133 g higher for neonates born to White mothers than those born to Black mothers. Barrett et al 15 found that Black women were more likely to have high T levels than White women, while Svensson et al 25 found that high T levels were inversely associated with birth weight and physical growth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, maternal testosterone levels cross the placenta have an effect on both placenta and the fetus. Indeed, maternal testosterone levels can affect fetal growth by increasing fetal testosterone levels and changing both maternal and placenta metabolism ( Svensson et al, 2019 ). Also maternal estrogens and the estrogen (aromatase) complex within the placenta facilitate the increase of blood flow to the gravid uterus and placenta ( Evans, 2007 ; Makieva et al, 2014 ), thus contributing to a normal fetal growth ( Escobar-Morreale et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%